Dynamics of maternal gene expression in Rhodnius prolixus - Pascual, Agustina (2021)
The study of the developmental processes in Rhodnius prolixus has recently advanced with the sequencing of the genome. In this work, we study maternal gene expression driving oogenesis and early embryogenesis in R. prolixus. We analyze the transcriptional profile of mRNAs to establish the genes expressed across the ovary, unfertilized eggs and different embryonic stages of R. prolixus until the formation of the germ band anlage (0, 12, 24, and 48 hours post egg laying). We identified 81 putative maternal and ovary-related genes and validated their expression by qRT-PCR. Consistent with a role in oogenesis and early development of R. prolixus, we show that parental RNAi against Rp-BicD results in embryos that did not show any distinguishable embryonic structure. In this framework we propose three hierarchies of maternal genes that affect early and late oogenesis, and embryonic patterning.